2001
DOI: 10.1016/s0735-1097(01)01112-3
|View full text |Cite
|
Sign up to set email alerts
|

Edge stenosis and geographical miss following intracoronary gamma radiation therapy for in-stent restenosis

Abstract: Edge restenosis following gamma irradiation treatment of ISR is related to GM: a mismatch between the segment of artery injured during the primary catheter-based intervention and the length of the radiation source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 76 publications
(17 citation statements)
references
References 18 publications
0
16
0
1
Order By: Relevance
“…The previous studies demonstrated that the geographic miss was strongly associated with the development of 6-month restenosis at the edge of irradiation segment [20,21]. However, the effect of geographic miss on late catch-up has not been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies demonstrated that the geographic miss was strongly associated with the development of 6-month restenosis at the edge of irradiation segment [20,21]. However, the effect of geographic miss on late catch-up has not been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Restenting, also, may contribute to late thrombosis [74]. Some studies have addressed that the most cause of restenosis after irradiation therapy is edge restenosis and geographical miss [75][76][77]. These unwilling results have proposed some other treatment modalities such as radioactive stents.…”
Section: Brachitherapymentioning
confidence: 99%
“…In fact, direct stenting and the use of glycoprotein IIb/IIIa failed to affect restenosis rates with metallic stents and drug-eluting stents. In contrast, the key factors considered essential in improving the results of VBT are adequate dosimetry and radiation coverage with wide margins to avoid geographical miss (16,17) and prolonged antiplatelet therapy to prevent late thrombosis. Nevertheless, the execution of these features was far from optimal; in the BRIDGE study, 21% of vessels had documented geographical miss, suggesting misplacement of the source in relation to the stent position.…”
Section: See Pages 520 and 528mentioning
confidence: 99%